The Efficacy of Lumbosacral Spine Phantom to Improve Resident Proficiency in Performing Ultrasound‐Guided Spinal Procedure - Kwon, So Young; Hong, Sang Hyun; Kim, Eun Sung; Park, Hue Jung; You, Youngjune; Kim, Young Hoon (Pain medicine (Malden, Mass.), 2015)
Objective To evaluate the efficacy of a lumbosacral spine phantom to improve novices' proficiency in performing ultrasound‐guided facet joint injection and medial branch block. Design and Setting Prospective study in a university hospital. Subjects In total, 30 participants with no experience of spinal ultrasonography were included and were allocated to one of two groups (control group, N = 10 and training group, N = 20). Methods A lumbosacral spine phantom was prepared using a lumbosacral spine model embedded in a mixture of gelatin and psyllium husk. All participants were tested (test‐1) following a basic education introductory program. Participants in the control group were then tested again after 1 week (test‐2). Those in the training group received a further 3‐h training, individually, and were tested again after 1 week (test‐2). Results The mean performance scores on test‐1 were 57.6 ± 6.0 in the control group and 57.3 ± 6.7 in the training group; and at test‐2, 61.0 ± 8.6 and 91.7 ± 4.9 (P < 0.001), respectively. The median time of performance at test‐1 was 158.3 ± 41.9 seconds in the control group and 185.3 ± 68.1 seconds in the training group; and at test‐2, 146.9 ± 38.9 seconds and 69.9 ± 22.0 seconds (P < 0.001), respectively. In the training group, the mean self‐rating level of proficiency scores were 2.2 ± 1.0 at pretraining, and 6.8 ± 0.8 at post‐training, respectively (P < 0.001). Conclusion Training using a gelatin‐based spine phantom helped novices to acquire the skills necessary to perform ultrasound‐guided lumbar facet joint injections and medial branch blocks.